2017
DOI: 10.1093/nar/gkx1264
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriophage DNA glucosylation impairs target DNA binding by type I and II but not by type V CRISPR–Cas effector complexes

Abstract: Prokaryotes encode various host defense systems that provide protection against mobile genetic elements. Restriction–modification (R–M) and CRISPR–Cas systems mediate host defense by sequence specific targeting of invasive DNA. T-even bacteriophages employ covalent modifications of nucleobases to avoid binding and therefore cleavage of their DNA by restriction endonucleases. Here, we describe that DNA glucosylation of bacteriophage genomes affects interference of some but not all CRISPR–Cas systems. We show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
1
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 65 publications
3
43
1
3
Order By: Relevance
“…Most sgRNAs used in this study showed low activity (Fig. 3a), and some DNA modifications on the genome of phages could also largely reduce the activity of sgRNA (17,33). Therefore, the fact that sgRNAs with low activity can be used for gene editing is significant and will greatly expand the editable locations of phage genome based on CRISPR technology.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…Most sgRNAs used in this study showed low activity (Fig. 3a), and some DNA modifications on the genome of phages could also largely reduce the activity of sgRNA (17,33). Therefore, the fact that sgRNAs with low activity can be used for gene editing is significant and will greatly expand the editable locations of phage genome based on CRISPR technology.…”
Section: Resultsmentioning
confidence: 89%
“…We failed to find a difference in sequence characteristics with high-activity and low-activity sgRNA, indicating that there are other inhibitors. For example, some DNA modifications on phage genomes and the DNA target site accessibility in eukaryotic cells have been proven to influence the activity of CRISPR/Cas9 (18,33). Therefore, a more complete investigation of the on-target activity of sgRNA on phages may be necessary.…”
Section: Resultsmentioning
confidence: 99%
“…A lack of protection by CRISPR immunity is not limited to jumbophages: E. coli strains carrying Type I-E CRISPR-Cas that were engineered to carry a single targeting spacer against different phages revealed a lack of protection against phages R1-37 (a giant phage) and T4 (125). The ability of phage T4 to by-pass Type I-E CRISPR immunity is at least in part attributable to their genome containing glucosyl-5-hydroxymethylcytosine instead of cytosine (126), and this cytosine modification also confers infectivity to the phage when bacteria have Type II-A CRISPR-based immunity (126,127), but not when they have Type V-A CRISPR-based immunity (126). Type I-E CRISPR-Cas offers protection against phage T7, but only under low phage densities; at high MOIs the cultures were lysed as efficiently as uninduced controls.…”
Section: -Temperate Phagementioning
confidence: 99%
“…T4 DNA ligase has a central role in the replication and repair of the phage genome during its infection of E. coli [43]. This also entails coping with DNA modifications such as the full substitution of cytosine for 5-hydroxymethylcytosine and glucosyl-5-hydroxymethylcytosine that naturally occurs in vivo [44,45]-this is a phage defence mechanism discussed below. Although its structure has only recently been determined [46], the mechanism of action of this enzyme has long been characterised [47].…”
Section: Common Molecular Biology Tools and Orthogonalitymentioning
confidence: 99%